Anaesthesia - related fears - a cross - sectional survey among the portuguese population - Pereira, C. (2018)
Introduction: Patients experience preoperative anxiety. The objective of this study was to assess patients’ fears concerning anaesthesia and evaluate possible associations with sociodemographic background and previous anaesthesia. Methods: A survey was filled preoperatively, for 6 months, including anaesthesia-related fears, sociodemographic data, previous anaesthesia and surgery, current surgical and anaesthetic procedure, and preferred anaesthesia technique. Descriptive statistics, principal component analysis, Chi-square test, t-test and ANOVA were used for statistical analysis. Results: 153 questionnaires were collected. The mean age was 58 years, 61.4% were female and 59.5% employed. 47.1% had an anaesthesia consultation before. 49.7% were ASA II. 78.4% had been submitted to surgery before, 81.7% to anaesthesia and 14.5% had regional anaesthesia. In 73.5% general anaesthesia preferred. Half of patients with previous regional anaesthesia favoured this technique. The most relevant fears were “being paralysed because of anaesthesia”, “not waking up” and “waking up during surgery”. The least relevant were “fasting incapacity”, “having nightmares” and “speaking of personal matters”. A statistically significant relation was observed between the fear of “feeling pain after surgery” and having a previous anaesthetic experience. Female and unemployed patients were more concerned with general complications, while male patients gave more importance to awareness and paralysis. Conclusion: Paralysis after anaesthesia, intraoperative awareness and death were the main concerns of our inquiries.